PENERAPAN STRATEGI CUSTOMER RELATIONSHIP MARKETING TERHADAP KEPUASAN NASABAH MENABUNG PADA BANK NAGARI - Fermayani, Riche; Basri, Alma Riyana (STIE Perbankan Indonesia, 2024)
This study aims to determine the effect of trust (trust), and commitment (commitment) on Customer Satisfaction Savings at Bank Nagari Siteba Branch. The data used is primary data, this study used 100 respondents as the research sample. The results showed that trust had a significant effect on Customer Satisfaction at Bank Nagari Branch Siteba, the commitment variable had a significant effect partially on Customer Satisfaction at Bank Nagari Branch Siteba. So the equation is obtained: Y = 3.056 + 0.632 X1 + 0.188 X2 + e The coefficient constant is positive by assuming the variable trust (trust), commitment (commitment) is considered non-existent or has a value of zero, then Customer Satisfaction is still there at 3.056, the regression coefficient for the variable trust (trust) (X1) has a positive value of 0.632 regression coefficient of commitment (commitment) (X2) has a positive value of 0.188 8. Adjusted Square value of 0.785 which means that all variables have an influence of 78.5% on customer satisfaction. while the remaining 21.5% is explained by other variables not examined in this study. Keywords: Trust, Commitment, Customer Satisfaction.